Survey of plants used by the Itawis in traditional health care practices in Basi, Solana, Cagayan with notes on lethality activity using brine-shrimp (artemia samila) bioassay - Sarah Sophia M. Mendoza. 4 0 16; 5 (2017)
u
Thesis:(B.S. Biology)- Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2